Ecology culture and heritage of the nature preservation of kazakh people (Journal of Philosophy Culture and Political Science, 2018)
Variety and frequency of natural and social changes and their globalization makes us to think about humanity’s further ability of existence. One of the main issues of humanity for today is finding effective ways to resolve ecological problems. Ecology of culture is main factor which regulates harmony of close interrelation between a man and society, a man and nature, a man and civilization. Along with it, it is one of the vital cultural anthropology phenomenons which provide humanity with cultural spiritual heritage. The whole complex of material practical service in relation of a society to the nature made even more important the issue its interrelation with ecological consciousness. In this article is considered how Kazakh people could understand secrets of the nature and preserve it. It is clear that nations with its specific development history has ecology culture concept with deep philosophical and cultural meaning. It is clear that this concept was a historical process which identifies function of stable social construction. Any cosmology elements such as cultural norms, dogmas, axiology systems, saint rituals and traditions serve as mechanisms for preservation of a society. Ecology of culture with its exogeneous peculiarity which is directed to support harmony with the nature, being dependent on cosmic strings, can be considered as the main element of social life. As such it identifies social stability in dynamics of social life’s historical development and its transformation of adaption to environmental influences. Key words: cultural values, ecological culture, nomadic people, nomads.